2019
DOI: 10.2224/sbp.7597
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and Chinese family-owned small- and medium-sized enterprises

Abstract: We investigated corporate social responsibility (CSR) cognitions and practices in Chinese family-owned small- and medium-sized enterprises. We explored the internal mechanisms of CSR on the basis of the quantitative data we obtained from managers and owners of these enterprises, and industry experts. The results showed that CSR cognitions significantly influenced CSR motivations, which, in turn, influenced CSR practices, and that the relationship between CSR cognitions and practices was mediated by CSR motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…16. CSR practices vary depending on the FF's industry [58]. Thus, sustainability in FFs is largely influenced by the social relationship between family members and market pressures.…”
mentioning
confidence: 99%
“…16. CSR practices vary depending on the FF's industry [58]. Thus, sustainability in FFs is largely influenced by the social relationship between family members and market pressures.…”
mentioning
confidence: 99%
“…In other words, venture capitalists are not motivated by the opportunities to participate in the management of those firms which they invested, but they are more motivated by the changes in the firm's market valuation. In addition, because most small and medium-sized listed firms are family businesses (Xue et al, 2019), family managers and VC institutions may encounter conflict or internal friction which can make decision-making inefficient (Jia et al, 2020). This reduces the ability of listed firms to make timely decisions on internal control, thus making their performance worse.…”
Section: Regression Analysismentioning
confidence: 99%
“…Research on CSR in family SMEs in China, published by Xue, Yu, Xu (2019), showed that in terms of overall knowledge of CSR, 96% of participants said they had heard of CSR or equivalent concepts. The most important parameters of CSR were health and safety and the business environment.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…In comparison with medium-sized enterprises, our research recorded a drop of 19.5% with a result of 41.5% (22 out of 53) compared to research in 2008 with a value of 61%. In the case of Chinese family SMEs (Xue, Yu, Xu, 2019), up to 96% of respondents heard about the concept of CSR. Contrary to the opinions published by Pavlík and Bělčík (2010) of CSR activities -especially sponsorship -our results are in conflict, because only 13% of respondents work socially responsibly in the community (support for corporate giving).…”
Section: Discusionmentioning
confidence: 99%